2008
DOI: 10.1016/j.joca.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of interleukin-4 decreases nitric oxide production by chondrocytes and ameliorates subsequent destruction of cartilage in instability-induced osteoarthritis in rat knee joints

Abstract: The present study suggests that IL-4 may exert chondroprotective properties against mechanical stress-induced cartilage destruction, at least in part, by inhibiting NO production by chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 41 publications
1
48
0
1
Order By: Relevance
“…IL-4 is an anti-inflammatory cytokine with important cartilage anabolic effects, because it avoids proteoglycan depletion and chondrocyte apoptosis [44][45][46]. This cytokine is paramount for cartilage health and its expression is in reduced osteoarthritic cartilage [6].…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 is an anti-inflammatory cytokine with important cartilage anabolic effects, because it avoids proteoglycan depletion and chondrocyte apoptosis [44][45][46]. This cytokine is paramount for cartilage health and its expression is in reduced osteoarthritic cartilage [6].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, IL-4 can induce upregulation of the expression of TNF α receptors, such as TNF-R1, and TNF-R2 [200]. In addition to a direct decrease in the secretion of inflammatory cytokines, there is also a decrease in the secretion of other inflammatory mediators such as PGE2, COX-2, PLA2, and iNOS [191, 197, 200, 201]. It seems reasonable to cite a study, which analyzed the effect of rmIL-4 (recombinant mouse IL-4) in combination with rmGM-CSF for the dendritic cells CD11b + F4/80 + iDC in a mouse model, where inflammatory joint disease was induced artificially [202].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…A study utilizing a rat model of instability-induced experimental OA has reported that IL-4 may have a chondroprotective effect in mechanical stress-induced OA through suppressing nitric oxide production by chondrocytes and preventing cartilage destruction following intra-articular injection. 131 The use of biomaterial scaffolds for localized delivery of anti-inflammatory proteins may be a beneficial strategy to antagonize pro-inflammatory mediator production in an osteoarthritic joint, and subsequently counteract the negative influence of pro-inflammatory mediators on cartilage regeneration.…”
Section: Anti-inflammatory Protein Deliverymentioning
confidence: 99%